2018
DOI: 10.1007/s00432-017-2576-2
|View full text |Cite
|
Sign up to set email alerts
|

Microarray profiles reveal that circular RNA hsa_circ_0007385 functions as an oncogene in non-small cell lung cancer tumorigenesis

Abstract: In summary, results suggest hsa_circ_0007385 plays a role in NSCLC tumorigenesis, providing a potential therapeutic target for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 26 publications
6
77
0
Order By: Relevance
“…The identification of new molecular mechanisms underlying the immune response has prompted many researchers to explore the involvement of these mechanisms in sustained inflammation in DKD. 20) Our study delineated a critical role of circRNA in glucose-induced inflammation and fibrosis in proximal tubular cells. Noncoding RNAs (ncRNAs) have attracted more attention than ever.…”
Section: Discussionmentioning
confidence: 75%
“…The identification of new molecular mechanisms underlying the immune response has prompted many researchers to explore the involvement of these mechanisms in sustained inflammation in DKD. 20) Our study delineated a critical role of circRNA in glucose-induced inflammation and fibrosis in proximal tubular cells. Noncoding RNAs (ncRNAs) have attracted more attention than ever.…”
Section: Discussionmentioning
confidence: 75%
“…For example, Zong et al showed that circRNA_102231 was increased and could act as a potential biomarker and therapeutic target for lung cancer patients [9]. Jiang et al [10] indicated that circular RNA hsa_circ_0007385 could function as an oncogene in nonsmall cell lung cancer tumorigenesis. Wan et al [11] indicated that circular RNA-ITCH suppressed lung cancer proliferation via inhibiting the Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…22 A variety of circRNAs affect lung cancer invasion and migration by regulating related targets, such as hsa_circ_0007385, circ-BANP, and circPTK2. [23][24][25] In our study, the overexpression of circ-IGF1R in lung cancer cells inhibited cell migration and invasion and interfered with the ability of circ-IGF1R to promote cell invasion and migration. However, IGF1R displays potent antiapoptotic, prosurvival capacities and plays a key role in malignant transformation.…”
Section: Discussionmentioning
confidence: 55%
“…Tumor metastasis is a multistage process, which is regulated by several genes, including metastasis‐associated genes and metastasis‐suppressing genes . A variety of circRNAs affect lung cancer invasion and migration by regulating related targets, such as hsa_circ_0007385, circ‐BANP, and circPTK2 . In our study, the overexpression of circ‐IGF1R in lung cancer cells inhibited cell migration and invasion and interfered with the ability of circ‐IGF1R to promote cell invasion and migration.…”
Section: Discussionmentioning
confidence: 55%